Sustaining the Specialty Coffee in Morocco: Challenges and Opportunities - Kurniawan Arif Maspul (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Morocco's long gastronomy history creates it unique for tourists who visit the country from time to time. In addition, developing specialty coffee in the Middle East requires Morocco to follow the third-wave coffee culture. Therefore, in sustaining specialty coffee in Morocco, the community, especially youth, participates in cultivating this third-wave culture, apart from following global economic trends and developing communities in coffee knowledge from farm to cup. The author's visit to Morocco to explore the uniqueness of specialty coffee and discover its new coffee cultures in the region for the last four years. This report is qualitatively based on observations from visits and interviews with Hajar Jeddou, one of the coffee professionals in Morocco. Keywords: Specialty Coffee, Creative Economy, Gastronomy, Tourism Development